Manajemen Sumber Daya (Biaya dan Sarana Prasarana) pada Lembaga Pendidikan Islam: Memastikan Efisiensi dan Keberlanjutan Operasional - Ihsan Izdihara Harum; M Ikhsan Fauzi H; Ardhiva Fachrul Adji; Deden M Ismail; Adi Rosadi (CV Edujavare Publishing, 2024)
Resource management, especially in the context of costs and infrastructure, is an important aspect in maintaining the operational continuity of Islamic educational institutions. This article outlines the crucial role of resource management in ensuring the efficiency, effectiveness, and sustainability of Islamic educational institutions. Using an in-depth structured research approach, this article analyzes theories, best practices, and challenges faced in cost management and infrastructure. Emphasis is placed on the importance of prudent management of budgets, maintenance of facilities, and development of resources in line with Islamic values.